PRDM1 expression on the epithelial component but not on ectopic lymphoid tissues of Warthin tumour - Wang, Y; Zhou, J; Zhang, Y; Wang, L; Liu, Y; Fan, L; Zhu, J; Xu, X; Huang, G; Li, X; Xun, W (Oral diseases, 2015)
Objective To determine the role of PRDM1, a key molecule for modulating the immune cells, in Warthin tumour (WT) pathogenesis. Subjects and methods Forty paraffin‐embedded parotid tissues of patients (mean age: 62.08 ± 11.90) with WT were retrieved from the pathology archives of Qindu Hospital from January 2012 to December 2012. The PRDM1 expression was investigated in a cohort of WT by immunohistochemistry. Results PRDM1 was expressed only on the epithelial component but not on ectopic lymphoid tissue of the tumour. Statistically, PRDM1 expression rates between WT glandular epithelial cells (40/40 cases) and the tumour‐adjacent tissues (0/9 cases), and WT germinal centres (0/34 cases) and tonsil tissues (10/10 cases) were significantly different (P < 0.001), respectively. Conclusions The PRDM1 expression appeared to play an essential role in WT pathogenesis. A better understanding of it might give options for revealing possible novel management strategies.